Measuring the Level of Prevalence of Undernourishment (PoU): Analysis of SDGs Achievement in Indonesia - Iwang, Baso; Sa'at, Nor Hayati binti; Anwar, Andi Faisal; Rusydi, Bahrul Ulum (EKO-REGIONAL, 2024)
Prevalence of Undernourishment (PoU) is an indicator that measures the achievement of the 2nd goal of the Sustainable Development Goals (SDGs) agenda. Ideally, Indonesia as an agricultural country is able to guarantee the availability of food supplies and people's access to nutritious food products becomes easier. However, since 2018-2022 the prevalence of undernourishment (PoU) in Indonesia has continued to increase from year to year. Therefore, this study aims to determine the factors that influence the level of Prevalence of Undernourishment (PoU) in Indonesia through food expectations, producer price index, food security budget, people's purchasing power and social assistance in the food sector. The novelty of this research is to try to trace the relationship between the dimensions of food quality, fiscal policy, price policy and people's purchasing power to the prevalence of undernourishment in Indonesia. To achieve this goal, a multiple regression analysis method was used with secondary data from 2011-2022 or the period before and after the implementation of the Sustainable Development Goals (SDGs) agenda in Indonesia. The results of the study show that the producer price index, food security budget and people's purchasing power have a significant effect on the level of Prevalence of Undernourishment (PoU) in Indonesia. Meanwhile, food expectations and social assistance in the food sector have no significant effect on the level of Prevalence of Undernourishment (PoU) in Indonesia. Implication of this research, the government needs to evaluate various food security programs in order to maximize the reduction of the prevalence of undernourishment (PoU) in Indonesia.